Fifty Years of Segregation : Black Higher Education in Kentucky, 1904-1954 - Hardin, John A., 1948- (Book collections on Project MUSE., 1997)
Kentucky was the last state in the South to introduce racially segregated schools and one of the first to break down racial barriers in higher education. The passage of the infamous Day Law in 1904 forced Berea College to exclude 174 students because of their race. Throughout the 1930s and 1940s black faculty remained unable to attend in-state graduate and professional schools. Like black Americans everywhere who fought overseas during World War II, Kentucky's blacks were increasingly dissatisfied with their second-class educational opportunities. In 1948, they financed litigation to end segre.